Hand-lettering ledger - McDevitt, Mary Kate, ....- (San Francisco : Chronicle Books, 2014)
The ultimate tool for designers and creatives looking to tap into the trend of hand-drawn lettering, this workbook features step-by-step lessons on a range of styles plus more than 120 practice pages, making it the ideal place to learn and perfect this in-demand design skill.